BEHAVIOUR OF SUPERCONDUCTING FAULT CURRENT LIMITER UNDER FAULT CONDITION - KARUNA L. BARI,; S. M. SHEMBEKAR, (International Journal of Innovations in Engineering Research and Technology, 2021)
Now a days due to increase in electricity demand for the purpose of industrialization, agriculture, domesticand educational etc there exists more chances of fault occurance. The Faults occurs due to insulation damaging, breaking of conductor, short circuit, lightning etc. Till now we used various mechanicaldevices for protection purpose of a transmission line against fault like a relay, circuit breakers etc.But it is impossible to reduce the magnitude of fault current totally. So in addition to circuit breaker another electrical device is connected in series in a network called as superconducting fault current limiter i.e SFCL. The elimination ofthe fault current completelyis not possible, but we canminimize the fault current in large amount by using SFCL